Synchronization of Financial Cycles in selected Central and Eastern European Countries - Robert A. GRECU (Communications of International Proceedings, 2022)
The COVID-19 pandemic had a strong economic impact, but its effects were felt also in the financial area. As a result of the economic recovery in 2021, there has been registered a significant growth of the lending activity in Central and Eastern European countries. This study illustrates that these increases have generated, for countries such as Hungary, the re-entry of the financial cycle in the expansion phase, being recorded positive deviations of credit from its long-term trend, situation which was not seen since the period before the last financial crisis. The results of the analysis also show that the financial cycle has a longer duration compared to the business cycle, as well as a higher amplitude. Thus, the turning points of the financial cycle are rarer, but they generate stronger effects than those of the business cycle. Regarding the synchronization of financial cycles at the level of the analyzed CEE countries, the results of this paper illustrates a strong correlation between the financial cycles of Romania, Bulgaria, and Hungary.
Keywords: financial cycle; synchronization; CEE countries.